Analysis of spike protein variants evolved in a novel in vivo long-term replication model for SARS-CoV-2 - Kim, Dongbum; Kim, Jinsoo; Kim, Minyoung; Park, Heedo; Park, Sangkyu; Maharjan, Sony; Baek, Kyeongbin; Kang, Bo Min; Kim, Suyeon; Park, Man-Seong; Lee, Younghee; Kwon, Hyung-Joo (Frontiers in Cellular and Infection Microbiology, 2023)
The spectrum of SARS-CoV-2 mutations have increased over time, resulting in the emergence of several variants of concern. Persistent infection is assumed to be involved in the evolution of the variants. We established a novel in vivo long-term incubation model using xenografts of Calu-3 human lung cancer cells in immunodeficient mice. After infection with parental SARS-CoV-2, viruses were found in the tumor tissues for up to 30 days and acquired various mutations, predominantly in the spike (S) protein, some of which increased while others fluctuated for 30 days. Three viral isolates with different combination of mutations produced higher virus titers than the parental virus in Calu-3 cells without cytopathic effects. In K18-hACE2 mice, the variants were less lethal than the parental virus. Infection with each variant induced production of cross-reactive antibodies to the receptor binding domain of parental SARS-CoV-2 S protein and provided protective immunity against subsequent challenge with parental virus. These results suggest that most of the SARS-CoV-2 variants acquired mutations promoting host adaptation in the Calu-3 xenograft mice. This model can be used in the future to further study SARS-CoV-2 variants upon long-term replication in vivo.